Organisation of lease accounting in accordancewith international financial reporting standard (Вестник КазНУ. Серия Экономическая, 2016)
In accordance with International Financial Reporting Standard (IAS) 17, “Leases” is reflected establishment of discipline in determining the appro priate accounting policies and the composition of information,subjected to disclosure, in relation to rental agreements of the lessees and lessors. Due to the nature of the activities,realized under the rental agreements, the standard is appliedin relation to agreements, providing transfer of rights to use assets, even, despite the fact that the exploitation of such assets may require the lessor torender significant services, related to the maintenance of given assets. The characteristics of applied terms and the questions of organisation oflease accounting for lessee and lessor are considered. Also standard is disclosed methods, used to determine the incomes and ex penses on a lease agreement from both the lessor and the lessee side, that will be recognized in the current and following periods.